Personality Of Main Character In Jobs Film Directed By Joshua Michael Stern - Sayyid Khairunas; Rizky Mirani Desi Pratama; Esa Suci Wardani (Wanastra: Jurnal Bahasa dan Sastra, 2018)
The purpose of this analysis is to know the personality of a person through a film. the author will discuss about the personality and nature of the main character in the film Jobs directed by Joshua Michael Stern. this paper contains how Steve personality in this movie. What are his personality types and moral values that can be taken and the author uses two relevant theories to analyze this film. The method of analysis is qualitative descriptive method. The data were collected through repeated witnessing and the theory for analysis here was obtained by books from library research and internet media in the form of electronic books. the results of f analysis show that (1) there are five personality data shown in the film (2) are seven data of personality type based on Goldberg's theory of Openness, Conscientiousness, Agreeableness, Extroversion and Neuroticism (3) moral values can be taken from film, that people can think of it as a lesson. The study of the analysis is useful for understanding the basic personality of each person and how good personality can affect a person's life in the field of work.